FAKTOR INTERNAL PERUSAHAAN YANG MEMPENGARUHI KEBIJAKAN LINDUNG NILAI - Ranny Junia Setiawan (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2019)
Hedging is used to protect the value of a company’s assets or liabilities from exposure to fluctuations in the value of foreign currency. This study aims to investigate the conditions and influence of firm size, growth opportunities, leverage ratio, and financial distress either simultaneously or partially to the hedge policy of BUMN listed in the IDX period of 2013-2016. The sample in this study was chosen based on purposive sampling method, obtained from 16 BUMN companies with research period from 2013-2016. Data analysis technique in this research is descriptive statistical analysis and logistic regression analysis. The results of this study indicate that firm size, growth opportunities, leverage, and financial distress simultaneously have a significant effect on hedging policy. Partially, firm size and financial distress have a significant positive effect on hedging policy, leverage has a significant negative effect on hedging policy, while growth opportunity has a positive effect not significant to hedging policy.